Advancing Equal Protection and Regulatory Solutions for an Inclusive Civic Education - Charles Berebon (Amicus Curiae: Journal of Law and Justice Dialogue, 2025)
This article explores the teaching of civic engagement in academic environments, focusing on its potential to generate new knowledge and inspire social and personal action. It advocates for regulatory measures to ensure a fair and balanced curriculum that supports diverse perspectives and fosters productive discourse, encouraging active student participation in civic life. Rooted in the Fourteenth Amendment’s equal protection clause, which guarantees equal treatment and opportunities, the article underscores the importance of giving all students a well-rounded education. Applying these principles, the article calls for a more equitable civic education system that empowers students to contribute meaningfully to their communities. The proposed regulatory remedies aim to create a curriculum that embraces diverse worldviews, promoting open and respectful discussions among students. This inclusive approach fosters critical thinking and helps students gain a deeper understanding of different perspectives, which can enhance their civic engagement. Additionally, the article highlights the need for safeguards against biased or exclusionary educational practices, ensuring that all students, regardless of background or belief, have equal access to educational opportunities. Dismantling barriers and fostering fairness will help equip students with the knowledge and skills needed to participate in their communities actively. Through the lens of the Fourteenth Amendment’s equal protection, the article advocates for legal and regulatory solutions that ensure a well-rounded, balanced curriculum that reflects a broad range of worldviews.